Reversible and Tunable Second‐Order Nonlinear Optical Susceptibility in PZT Thin Films for Integrated Optics (Advanced Optical Materials 16/2021). Issue 16 (18th August 2021) - Feutmba, Gilles F.; Hermans, Artur; George, John P.; Rijckaert, Hannes; Ansari, Irfan; Van Thourhout, Dries; Beeckman, Jeroen
Abstract : A laser beam passing through a thin ferroelectric lead zirconate titanate (PZT) film is transformed into a beam with doubled frequency by means of second harmonic generation. The polarization density of the PZT film and the second‐order susceptibility can be controlled and reserved by means of an applied voltage. The thin film exhibits a very strong susceptibility of 128 pm/V, which opens avenues for highly efficient and tunable on‐chip nonlinear devices. For further details, see article number 2100149 by Gilles F. Feutmba, Jeroen Beeckman and co‐workers.